Features of the Silo Capacities’ Calculation at the Unsymmetrical Wind Load - Pichugin, Sergei; Makhinko, Natalia (International Journal of Engineering and Technology, 2018)
The paper deals with summarizing research concerning analytical technique of calculation of vertical cylindrical capacities for grain storage under the influence of unsymmetrical wind influences. In particular, the analysis of vertical stiffenersâ€™ work was conducted and illustrated the body deformation for high and low capacities, depending on the number of rigid elements. Considering the constructionâ€™s form, which is an axially-symmetric shell of rotation, the main equations for determining efforts, displacements and the series of calculation coefficients were formed. Considering the character of the wind loadâ€™s influence, there were also made propositions considering defining normal and tangential strains in cross-section, longitudinal directions and also radial, circular and longitudinal displacements, accordingly to the general theory. was made The graphical nomograph for the convenient calculation, which could be used as an alternative when searching for intermediate calculation functions was made. In addition, capacities with different edgesâ€™ fortification are considered, for example, strengthened by absolutely rigid circle, free or fixed by elastic circle. General assessment of the total deflected mode of the capacityâ€™s construction was made, depending on the number of decomposition coefficients, which were put in calculation. Conclusions are accompanied with graphic isometric understandings, which were obtained on the basis of practical calculation.Â Â Â